Aplikasi Pembelajaran Al-Qur’an "Madina" Memanfaatkan Teknologi Digital Pada Anak Usia Dini Berbasis Android Menggunakan Metode Rapid Application Development - Musliadi KH; Kaharuddin Kaharuddin; Yuni Roza; Yonky Pernando (Journal of Information System Research (JOSH), 2025)
Learning the Qur'an is the most important aspect in shaping a person's personality and morality, including in early childhood, especially those who adhere to Islam. Currently, the level of interest in learning the Qur'an in early childhood has decreased in various circles due to the influence of technological developments. Technological developments have changed children's behavior and attitudes in everyday life, especially in the use of smartphones which are more often used to play and watch movies via YouTube, Instagram, and Facebook than used to learn to read the Qur'an so that knowledge about reading the Qur'an is eliminated due to playing and watching movies. Along with the increasing influence of technology among children, there needs to be a breakthrough that can be utilized in learning the Qur'an in early childhood without changing the behavior of using smartphones. To design the "Madina" Qur'an learning, an appropriate, fast, and effective method is needed as a benchmark in the design cycle. The Rapid Application Development method is one of the many methods that are most often used to design Android-based applications, this is because this method only consists of four main cycles and focuses on the use of a short time in the design process. The results of the research and evaluation conducted obtained 54 respondents who were dominated by parents as the main companions in using smartphones. Children who use this application the most are in the age range under 4 years where on average they use the application for approximately 15-30 minutes under parental supervision. The Al-Qur'an learning application "Madina" can be accepted by users and parents, this is indicated by the evaluation results being at an average percentage of 86% with very strong criteria.